An Augmented Static Olley–Pakes Productivity Decomposition with Entry and Exit: Measurement and Interpretation. (6th August 2015) - Maliranta, Mika; Määttänen, Niku
Abstract : We develop an augmented Olley–Pakes (OP) decomposition that allows us to examine how entering and exiting firms contribute to the popular OP covariance measure of allocative efficiency. Applying the decomposition to a comprehensive micro‐level data, we find that a large part of the OP covariance component can be attributed to entrants and exiting firms. We also build a model of firm dynamics that is consistent with our main empirical results. In the model economy, the standard OP covariance component tends to increase with certain type of distortions because of endogenous changes in firm entry and exit.